Strategi Digital Public Relations Dalam Menyampaikan Informasi Melalui Instagram @bdg.disdik - Devina Putri, Resha; Khoirudin, Khoirudin (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to identify and describe the strategy of Digital Public Relations in conveying information via Instagram @bdg.disdik based on the perspective of the concept of The Circular Model of Some put forward by Regina Luttrell. The method used is descriptive with a qualitative approach which in its implementation goes through several stages, namely observation, in-depth interviews and documentation. The results of this study indicate that the Digital Public Relations strategy in conveying information via Instagram @bdg.disdik is in accordance with the four aspects of The Circular Model of Some with indicators: First, the share stage is carried out by utilizing various features to attract public participation, provide feedback as an effort to connect with the public, build trust. Second, the optimize stage is carried out by providing an in-depth understanding of the public and building interaction through uploading information content. Third, the manage stage is carried out by monitoring Instagram's performance through media monitoring and presenting actual information in real time. Fourth, the engage stage is carried out by setting targets based on the relevance of the information context, as well as collaborating on content.